Analysis of memristor based ring oscillators for hardware security - Hashim N.A.B.N.; Hamid F.A.B.; Teo J.; Hamid M.S.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
CMOS integrated circuits; Cryptography; Energy efficiency; Fighter aircraft; Hardware; Memristors; Metals; MOS devices; Number theory; Oscillators (electronic); Oxide semiconductors; Random number generation; Reconfigurable hardware; Resistors; SPICE; Complementary metal oxide semiconductor process; Cryptographic security; Memristor; Random number generators; Ring oscillator; security; Security application; Unique identifications; Hardware security